A method for preparing a bio-based supported superacid solid catalyst

Through the preparation method of bio-based supported super acid solid catalyst, the problems of cumbersome preparation process and reduced catalytic activity in the prior art are solved, and efficient and environmentally friendly catalyst preparation and use are achieved.

CN119733534APending Publication Date: 2025-04-01ANHUI TAIGE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925544.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The preparation process of solid acid catalysts in the prior art is complicated and may easily cause the problem of reduced catalytic activity after long-term use.

Method used

Using the preparation method of bio-based supported super acid solid catalyst, a supported super acid bio-based catalyst with high catalytic activity and structural stability is prepared through the steps of carbonization, sulfonation and electrochemical deposition of biomass raw materials.

Benefits of technology

It realizes efficient preparation and long-term stable use of catalysts, reduces reaction energy consumption and pollutant generation, and has environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733534A_ABST
    Figure CN119733534A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of bio-based catalysts, and specifically to a method for preparing a bio-based supported superacid solid catalyst, comprising the following steps: S1, carbonization of biomass raw materials, S2, sulfonation of biomass, S3, loading treatment of bio-based catalysts, and then obtaining a supported superacid bio-based catalyst. The supported superacid bio-based catalyst is obtained by loading superacid groups on biomass as raw materials after incomplete carbonization, and has acid catalytic performance equivalent to sulfuric acid. The bio-based material can effectively form an efficient spatial structure, has the advantages of stable structure and high specific surface area, and can be easily separated from liquid products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bio-based catalysts, and in particular to a method for preparing a bio-based supported superacid solid catalyst. Background Art

[0002] Acrylate molecules contain semi-conjugated vinyl double bonds and carboxyl-derived functional groups, which give them active chemical properties and make them easy to undergo polymerization reactions. Acrylate is an important monomer of high molecular weight polymers and is widely used in copolymerization reactions to produce polymers with different properties. It is used in many fields such as cosmetics, medicines, coating thickeners, and photocurable materials.

[0003] For example, in industry, concentrated sulfuric acid is often used as a catalyst for the esterification reaction of alcohols and acids. Although sulfuric acid has the advantages of good catalytic effect and low production cost, it is difficult to separate the catalyst from the product. Phosphotungstic acid is another strong proton solid acid, which is also used as a catalyst for reactions such as esterification. It has the advantages of high catalytic activity and no by-products. However, the reusability of phosphotungstic acid is poor, which limits its application in industry.

[0004] The solid acid catalyst of the present invention, as a new type of superacid catalyst, shows unique advantages in the synthetic ester reaction of alcohol acid esterification. They are easy to separate from the product, which is conducive to simplifying the production process and improving product quality. The active component and carrier of the solid acid catalyst can be flexibly selected to adapt to different reaction conditions and requirements. The supported solid acid catalyst is a type of catalyst prepared by loading the active component on a specific carrier. Its activity and life span are affected by multiple factors such as the active component, carrier and reaction process conditions.

[0005] With the improvement of environmental protection requirements, the application of solid acid catalysts in the synthesis of acrylates has received more and more attention. Solid superacids such as immobilized heteropolyacids have the advantages of high catalytic activity, good selectivity, and fast regeneration speed, and have become a research hotspot in this field. In the future, the research on solid acid catalysts will pay more attention to the activity, stability and environmental friendliness of the catalyst to meet the actual needs of industrial production. The preparation process of solid acid catalysts in the prior art is cumbersome, and the catalytic activity is prone to decrease after long-term use. In view of this, we propose a method for preparing a bio-based supported superacid solid catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a bio-based supported superacid solid catalyst, which solves the shortcomings of existing acrylate reaction catalysts.

[0007] The principle of the invention is as follows: the hydrophobic surface on the bio-based supported superacid solid catalyst can reduce the adsorption of water and increase the adsorption of acid and alcohol, thereby improving selectivity and reaction efficiency; the sulfonic acid group obtained by the biochar carrier after the sulfonation reaction can provide a high concentration of strong acid sites to obtain a considerable reaction rate under synthesis conditions; in the carbonization process, ZnCl2 can be used as an activator to promote the carbonization of biomass raw materials and as a template for forming a mesoporous structure; the bio-based superacid solid catalyst forms metal nanoparticles on the catalyst surface through electrochemical deposition, and the fluffy bio-based superacid solid catalyst is connected by the metal nanoparticles, so that the catalyst can form a network structure when it is unfolded, which is convenient for the catalyst to be recovered after the reaction is completed. At the same time, the metal nanoparticles also have certain catalytic performance for the synthesis reaction of acrylate, so the metal nanoparticles are loaded on the bio-based superacid solid catalyst without reducing the number of sulfonic acid groups to improve the synthesis efficiency of acrylate.

[0008] The present invention provides a method for preparing a bio-based supported superacid solid catalyst, comprising the following steps:

[0009] 1. A method for preparing a bio-based supported superacid solid catalyst, characterized in that it comprises the following steps:

[0010] S1. Carbonization of biomass raw materials: adding ZnCl2 to the dried biomass raw materials and uniformly mixing the ZnCl2 and the biomass raw materials; then putting the biomass raw materials into a heating device and heating and carbonizing them in a nitrogen environment; and cooling the carbonized biomass raw materials in a nitrogen environment until the temperature of the carbonized biomass raw materials drops to room temperature; then washing the biochar carrier with deionized water for 2-3 times, and drying to obtain the biochar carrier;

[0011] S2, sulfonation of biomass, putting the biochar carrier obtained after carbonization into a reactor, and adding an excess of sulfonating agent into the reactor, and obtaining a superacid bio-based catalyst after continuous reaction; wherein the ratio of the biochar carrier to the sulfonic acid group is 1g:2mL-1g:10mL;

[0012] S3. Loading treatment of bio-based catalysts: wrap the bio-based catalyst with a mesh polymer material and insert it into the electrolyte as a cathode. At the same time, insert the loaded metal into the electrolyte as an anode. Power is turned on for electrochemical deposition to electrolyze the loaded metal and form metal nanoparticles on the surface of the bio-based catalyst, thereby obtaining a loaded superacid bio-based catalyst.

[0013] Preferably, the biomass raw material in step S1 is a combination of one or more of corn cobs, rice straw, wood chips, bamboo chips, bagasse, and coconut shells;

[0014] Preferably, in step S1, the carbonization temperature of the biomass raw material is 200° C.-550° C., and the carbonization time is 0.5 hour-5 hours.

[0015] Preferably, the loaded metal selected in step S3 is one of Zn or Cu, and the electrolyte used in the reaction process is an acid solution of the anode metal;

[0016] The step S3 also includes removing the outer mesh polymer material after the reaction is completed, washing the supported superacid bio-based catalyst 2-3 times with deionized water, and drying after washing.

[0017] Preferably, the sulfonating agent used in step S2 is concentrated sulfuric acid, the mass fraction of the concentrated sulfuric acid is 98 wt %, the reaction temperature is 170° C.-220° C., and the reaction time of the sulfonation reaction is 6 hours-12 hours.

[0018] Preferably, the sulfonating agent used in step S2 is fuming sulfuric acid, the reaction temperature is 120° C.-170° C., and the reaction time of the sulfonation reaction is 6 hours-8 hours.

[0019] Preferably, the sulfonating agent used in step S2 is chlorosulfonic acid, the reaction temperature is 20° C.-50° C., and the reaction time of the sulfonation reaction is 6 hours-12 hours.

[0020] Preferably, the method further comprises a pretreatment step before step S1, specifically comprising: cutting, mixing, crushing and drying the biomass raw materials;

[0021] The particle size after crushing is 40 meshes to 80 meshes.

[0022] Preferably, the length of the biomass raw material after cutting is 3 cm to 4 cm, the drying temperature in step S1 and step S3 is 80° C. to 105° C., and the drying time is 3 hours to 5 hours.

[0023] By means of the above technical scheme, the present invention provides a method for preparing a bio-based supported superacid solid catalyst, which has at least the following beneficial effects:

[0024] (1) The present invention uses biomass as a raw material and then carries out incomplete carbonization to load super acidic groups, which has acid catalytic performance equivalent to sulfuric acid and a simple preparation process. At the same time, the supported super acid bio-based catalyst provided by the present invention is a bio-based material, which can effectively form an efficient spatial structure and has the advantages of stable structure and high specific surface area.

[0025] (2) The present invention can be easily separated from the liquid phase product by sedimentation or filtration. At the same time, since the catalytic activity does not decrease significantly, it can be used repeatedly. The catalytic activity is stable, which can reduce the reaction energy consumption and the generation of pollutants. It is expected to replace sulfuric acid and be widely used in esterification synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application:

[0027] Figure 1 Schematic diagram of the catalyst in Example 1 of the present invention;

[0028] Figure 2 This is a liquid chromatogram of TMPTA catalytically synthesized in Example 1 of the present invention;

[0029] Figure 3 This is a liquid chromatogram of EO3-TMPTA catalytically synthesized in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] A preparation method of a bio-based supported superacid solid catalyst is prepared by the following steps: firstly, pre-treating a biomass raw material, and firstly removing impurities from the biomass raw material during the pre-treatment: the biomass raw material is a combination of one or more of corn cobs, rice straws, wood chips, bamboo chips, bagasse, and coconut shells; placing the biomass raw material on a screen; continuously shaking the screen to separate impurities such as sand or soil adhered to the surface of the biomass raw material from the biomass raw material, thereby achieving the removal of impurities from the biomass raw material;

[0032] Secondly, the biomass raw materials are crushed: the biomass raw materials are cut into small segments of 3 cm to 4 cm in length, and the cut biomass raw materials are mixed and put into the crushing equipment, and the crushing is continued for 1 minute to 5 minutes to particles of 40 mesh to 80 mesh;

[0033] Then, the biomass raw material is washed: the crushed biomass raw material is put into the mixer, and washing water is added until the washing water covers the biomass raw material, and then the mixer is started, and the mixer continuously stirs the internal washing water and biomass raw material at a speed of 250 rpm for 30 minutes. The biomass raw material is continuously stirred in the washing water, and the biomass raw material is continuously washed. After repeating the washing 3 to 5 times, the washing operation of the biomass raw material is completed;

[0034] The biomass raw material is then dried: the raw material is put into the drying equipment and dried continuously at a drying temperature of 80°C-105°C for 3 hours-5 hours, the residual washing water on the surface of the biomass raw material is evaporated, and the biomass raw material is dried to a constant weight for use;

[0035] Then, the biomass raw material is preliminarily processed: the biomass raw material particles and ZnCl2 powder are added into the mixing equipment at a mass ratio of 1:2-1:5, and the mixing is continued for 10 minutes to 20 minutes to make the two solid particles evenly mixed;

[0036] Then, the biomass raw material is carbonized: the mixed biomass raw material is put into a heating furnace, and the temperature is raised to a carbonization temperature of 200°C-550°C at a nitrogen flow rate of 300 mL per minute and a heating rate of 10°C per minute, and the carbonization is carried out at a constant temperature of 0.5 hour to 5 hours, and the carbonized biomass raw material is cooled in a nitrogen environment until the temperature of the carbonized biomass raw material drops to room temperature;

[0037] The biomass raw material is washed 2-3 times with deionized water, and then dried at a drying temperature of 105° C. for 6 hours to obtain a bio-based carrier;

[0038] Sulfonation reaction of the bio-based carrier: the carbonized biomass raw material is put into the reactor, and an excess of concentrated sulfuric acid is added to the reactor at the same time, and the reaction is continued at a reaction temperature of 170°C-220°C for 6 hours-12 hours. After the sulfonation reaction is completed and the temperature inside the reactor drops to room temperature, the concentrated sulfuric acid and the product are separated, and after separation, deionized water is continuously injected into the reactor, filtered and washed, and 100°C deionized water is added to the reactor for washing again, and filtered until the pH value of the filtrate reaches 7.0, and then a supported superacid bio-based catalyst is obtained, and then the supported superacid bio-based catalyst is placed in an oven and dried at a drying temperature of 105°C for 6 hours;

[0039] Loading treatment of bio-based catalysts: copper sulfate is used as the electrolyte, and the bio-based catalyst is wrapped by a mesh polymer material and inserted into the electrolyte as the cathode. At the same time, a copper rod is inserted into the electrolyte as the anode. Power is turned on for electrochemical deposition, so that the copper rod is electrolyzed and deposited on the surface of the bio-based catalyst to form metal nanoparticles. After the deposition is completed, the bio-based catalyst is taken out of the electrolyte and the mesh polymer material is removed. The bio-based catalyst is washed with deionized water for 2-3 times and then dried at a drying temperature of 65°C for 12 hours to obtain a loaded superacid bio-based catalyst.

[0040] Example 1

[0041] First, the biomass raw material is pretreated. When the biomass raw material is pretreated, the biomass raw material is firstly removed from impurities: in this embodiment, corn cobs are selected as biomass raw materials, and the biomass raw material is placed on a screen. The screen is continuously shaken to separate impurities such as sand or soil adhering to the surface of the biomass raw material from the biomass raw material, thereby realizing the removal of impurities from the biomass raw material; corn cobs contain 54.5% sugar, 2.2% crude protein, 0.4% crude fat, 29.7% crude fiber, and 1.2% minerals. Polysaccharides, proteins, fats, and crude fibers as biomass raw materials can be used as good bio-based carriers after carbonization. At the same time, the structure of corn cobs is relatively loose, and a loose structure is formed after carbonization, thereby increasing the surface area of ​​the bio-based carrier, which is convenient for forming a catalyst with a high specific surface area after sulfonation;

[0042] Secondly, the biomass raw materials are crushed: the biomass raw materials are cut into small segments of 4 cm in length, and the cut biomass raw materials are mixed and put into the crushing equipment, and the crushing is continued for 5 minutes to 80 mesh size particles;

[0043] Then, the biomass raw material is washed: the crushed biomass raw material is put into the mixer, and washing water is added until the washing water covers the biomass raw material, and then the mixer is started, and the internal washing water and biomass raw material are continuously stirred at a speed of 250 rpm for 30 minutes. The biomass raw material is continuously stirred in the washing water, and the biomass raw material is continuously washed. After repeating the washing 5 times, the washing operation of the biomass raw material is completed;

[0044] The biomass raw material is then dried: the raw material is put into a drying device and dried continuously at a drying temperature of 105°C for 5 hours, the residual washing water on the surface of the biomass raw material is evaporated, and the biomass raw material is dried to a constant weight for later use;

[0045] Then, the biomass raw material was preliminarily processed: the biomass raw material particles and ZnCl2 powder were added into the mixing equipment at a mass ratio of 1:3, and the mixing was continued for 20 minutes to make the two solid particles evenly mixed;

[0046] Then, the biomass raw material is carbonized: the mixed biomass raw material is put into a heating furnace, and the temperature is raised to a carbonization temperature of 550°C at a heating rate of 10°C per minute under a nitrogen flow rate of 300 mL per minute, and the carbonization temperature is kept constant for carbonization for 5 hours, and the carbonized biomass raw material is cooled in a nitrogen environment until the temperature of the carbonized biomass raw material drops to room temperature;

[0047] The biomass raw material was washed three times with deionized water, and then dried at a drying temperature of 105° C. for 6 hours to obtain a bio-based carrier;

[0048] Finally, the bio-based carrier is subjected to a sulfonation reaction: the carbonized biomass raw material is put into a reactor, and an excess of concentrated sulfuric acid is added to the reactor at the same time, and the reaction is continued at a reaction temperature of 220°C for 12 hours. After the sulfonation reaction is completed and the temperature inside the reactor drops to room temperature, the concentrated sulfuric acid and the product are separated, and after separation, deionized water is continuously injected into the reactor, filtered and washed, and 100°C deionized water is added to the reactor for washing again, and filtered until the pH value of the filtrate reaches 7.0, and then a supported superacid bio-based catalyst is obtained, and then the supported superacid bio-based catalyst is placed in an oven and dried at a drying temperature of 105°C for 6 hours;

[0049] Loading treatment of bio-based catalysts: copper sulfate is used as the electrolyte, and the bio-based catalyst is wrapped by a mesh polymer material and inserted into the electrolyte as a cathode. At the same time, a copper rod is inserted into the electrolyte as an anode. Power is turned on for electrochemical deposition, so that the copper rod is electrolyzed and deposited on the surface of the bio-based catalyst to form metal nanoparticles. After the deposition is completed, the bio-based catalyst is taken out of the electrolyte and the mesh polymer material is removed. The bio-based catalyst is washed with deionized water for 3 times and then dried at a drying temperature of 65°C for 12 hours to obtain a loaded superacid bio-based catalyst.

[0050] Example 2

[0051] First, the biomass raw material is pretreated, and when the biomass raw material is pretreated, the biomass raw material is firstly removed from the impurities: in this embodiment, sawdust is selected as the biomass raw material, and the biomass raw material is placed on a screen, and the screen is continuously shaken to separate the impurities such as sand or soil adhering to the surface of the biomass raw material from the biomass raw material, thereby realizing the removal of impurities from the biomass raw material; sawdust is the sawdust and shavings powder left over from wood processing, and the proportion of lignin component is higher than that of corn cobs in Example 1. Lignin is insoluble in water and hydrophobic in its natural state. After the sulfonation reaction of the sulfonating agent, the lignin is converted into sulfonated lignin, which has very different properties from lignin. The introduction of sulfonic acid groups into lignin changes the polymer from neutral to an anion-containing active compound until it becomes one of the strongest known organic acids, with a dissociation constant of 0.3. At the same time, the sawdust and shavings powder are mostly thin in structure, and compared with corn cobs, sawdust can be processed into particles of a set size without excessive mechanical treatment;

[0052] Secondly, the biomass raw materials are crushed: the cut biomass raw materials are mixed and put into the crushing equipment, and crushed for 1 minute to particles of 40 mesh size;

[0053] Then, the biomass raw material is washed: the crushed biomass raw material is put into the mixer, and washing water is added until the washing water covers the biomass raw material, and then the mixer is started, and the mixer continuously stirs the internal washing water and biomass raw material at a speed of 250 rpm for 30 minutes. The biomass raw material is continuously stirred in the washing water, and the biomass raw material is continuously washed. After repeating the washing 3 times, the washing operation of the biomass raw material is completed;

[0054] The biomass raw material is then dried: the raw material is put into the drying equipment and dried continuously at a drying temperature of 80°C for 3 hours, the residual washing water on the surface of the biomass raw material is evaporated, and the biomass raw material is dried to a constant weight for later use;

[0055] Then, the biomass raw material was preliminarily processed: the biomass raw material particles and ZnCl2 powder were added into the mixing equipment at a mass ratio of 1:3, and the mixing was continued for 20 minutes to make the two solid particles evenly mixed;

[0056] Then, the biomass raw material is carbonized: the mixed biomass raw material is put into a heating furnace, and the temperature is raised to a carbonization temperature of 200°C at a heating rate of 10°C per minute under a nitrogen flow rate of 300 mL per minute, and the carbonization is carried out at a constant temperature of 0.5 hours, and the carbonized biomass raw material is cooled in a nitrogen environment until the temperature of the carbonized biomass raw material drops to room temperature;

[0057] The biomass raw material was washed three times with deionized water, and then dried at a drying temperature of 105° C. for 6 hours to obtain a bio-based carrier;

[0058] Finally, the bio-based carrier is subjected to a sulfonation reaction: the carbonized biomass raw material is put into a reactor, and an excess of fuming sulfuric acid is added to the reactor at the same time, and the reaction is continued at a reaction temperature of 120°C for 6 hours. After the sulfonation reaction is completed and the temperature inside the reactor drops to room temperature, the fuming sulfuric acid and the product are separated, and after separation, deionized water is continuously injected into the reactor, filtered and washed, and 100°C deionized water is added to the reactor for washing again, and filtered until the pH value of the filtrate reaches 7.0, and a supported superacid bio-based catalyst is obtained. Subsequently, the supported superacid bio-based catalyst is placed in an oven and dried at a drying temperature of 105°C for 6 hours;

[0059] Loading treatment of bio-based catalysts: copper sulfate is used as the electrolyte, and the bio-based catalyst is wrapped by a mesh polymer material and inserted into the electrolyte as a cathode. At the same time, a copper rod is inserted into the electrolyte as an anode. Power is turned on for electrochemical deposition, so that the copper rod is electrolyzed and deposited on the surface of the bio-based catalyst to form metal nanoparticles. After the deposition is completed, the bio-based catalyst is taken out of the electrolyte and the mesh polymer material is removed. The bio-based catalyst is washed with deionized water for 3 times and then dried at a drying temperature of 65°C for 12 hours to obtain a loaded superacid bio-based catalyst.

[0060] Example 3

[0061] First, the biomass raw material is pretreated. When the biomass raw material is pretreated, the biomass raw material is firstly impurity-removed: in this embodiment, the biomass raw material is coconut shell, the biomass raw material is placed on the screen, and the screen is continuously shaken to separate the impurities such as sand or soil adhering to the surface of the biomass raw material from the biomass raw material, thereby realizing the impurity removal operation of the biomass raw material;

[0062] Secondly, the biomass raw materials are crushed: the biomass raw materials are cut into small segments of 3.5 cm in length, and the cut biomass raw materials are mixed and put into the crushing equipment, and the crushing is continued for 3 minutes to 60 mesh particles;

[0063] Then, the biomass raw material is washed: the crushed biomass raw material is put into the mixer, and washing water is added until the washing water covers the biomass raw material, and then the mixer is started, and the mixer continuously stirs the internal washing water and biomass raw material at a speed of 250 rpm for 30 minutes. The biomass raw material is continuously stirred in the washing water, and the biomass raw material is continuously washed. After repeating the washing 4 times, the washing operation of the biomass raw material is completed;

[0064] The biomass raw material is then dried: the raw material is put into the drying equipment and dried continuously at a drying temperature of 95°C for 4 hours, the residual washing water on the surface of the biomass raw material is evaporated, and the biomass raw material is dried to a constant weight for later use;

[0065] Then, the biomass raw material was preliminarily processed: the biomass raw material particles and ZnCl2 powder were added into the mixing equipment at a mass ratio of 1:3, and the mixing was continued for 20 minutes to make the two solid particles evenly mixed;

[0066] Then, the biomass raw material is carbonized: the mixed biomass raw material is put into a heating furnace, and the temperature is raised to a carbonization temperature of 370°C at a heating rate of 10°C per minute under a nitrogen flow rate of 300 mL per minute for constant temperature carbonization for 3 hours, and the carbonized biomass raw material is cooled in a nitrogen environment until the temperature of the carbonized biomass raw material drops to room temperature;

[0067] The biomass raw material was washed three times with deionized water, and then dried at a drying temperature of 105° C. for 6 hours to obtain a bio-based carrier;

[0068] Finally, the bio-based carrier is subjected to a sulfonation reaction: the carbonized biomass raw material is put into a reactor, and an excess of chlorosulfonic acid is added to the reactor at the same time, and the reaction is continued at a reaction temperature of 35°C for 8 hours. After the sulfonation reaction is completed and the temperature inside the reactor drops to room temperature, the chlorosulfonic acid and the product are separated, and after separation, deionized water is continuously injected into the reactor, filtered and washed, and 100°C deionized water is added to the reactor for washing again, and filtered until the pH value of the filtrate reaches 7.0, and a supported superacid bio-based catalyst is obtained. Subsequently, the supported superacid bio-based catalyst is placed in an oven and dried at a drying temperature of 105°C for 6 hours;

[0069] Loading treatment of bio-based catalysts: copper sulfate is used as the electrolyte, and the bio-based catalyst is wrapped by a mesh polymer material and inserted into the electrolyte as a cathode. At the same time, a copper rod is inserted into the electrolyte as an anode. Power is turned on for electrochemical deposition, so that the copper rod is electrolyzed and deposited on the surface of the bio-based catalyst to form metal nanoparticles. After the deposition is completed, the bio-based catalyst is taken out of the electrolyte and the mesh polymer material is removed. The bio-based catalyst is washed with deionized water for 3 times and then dried at a drying temperature of 65°C for 12 hours to obtain a loaded superacid bio-based catalyst.

[0070] Comparative Example 1

[0071] The corn cob was pyrolyzed in a muffle furnace at 300°C for 3 h in a nitrogen atmosphere. 4 g of the biochar obtained by pyrolysis was mixed with 60 ml of concentrated sulfuric acid and stirred in an oil bath at 150°C for 12 h. After filtering, the filter residue was washed with hot deionized water and dried to obtain a biochar-based solid acid catalyst.

[0072] The specific surface area and pore volume analysis of Example 1, Example 2 and Example 3 were performed. The same weight of the above examples was weighed and placed inside a sample tube and the sample tube was installed on a pore size analyzer and a pore size measuring instrument. The specific surface area was calculated using the BET model at 5 relative pressure points between a relative pressure of 0.05 and 0.35, and the pore volume was calculated based on the cumulative nitrogen adsorption amount of the adsorption isotherm at a relative pressure of 0.99. The results are shown in the following table:

[0073]

[0074] It can be seen from the above table that Example 1, Example 2 and Example 3 all have a higher pore volume and a higher specific surface area. Therefore, when used as a catalyst for catalytic reaction, compared with the solid catalyst in the prior art, the same weight of the embodiments can increase the contact area between the reaction raw materials and the catalyst, thereby improving the catalytic reaction efficiency of the reaction raw materials.

[0075] Using Example 1, Example 2, Example 3 and Comparative Example 1 as catalysts, methyl acrylate was catalyzed and 4.8 g of methanol and 7.2 g of acrylic acid were mixed with 0.1 g of Example 1, Example 2, Example 3 and Comparative Example 1, respectively, and the reaction was continued at 75° C. for 1 hour.

[0076] Then, 10 mL of the filtered mixed solution was taken and titrated with 0.01 mol / L potassium hydroxide to obtain the amount of remaining acrylic acid. The ratio of the difference between the amount of remaining acrylic acid and the amount of initial acrylic acid to the amount of initial acrylic acid was the reaction yield of methyl acrylate. The results are shown in the following table:

[0077]

[0078] Taking Example 1 as an example, the supported superacid bio-based catalyst Example 1 was used as a catalyst, and acrylic acid was used as a raw material for a catalytic reaction to generate a catalytic synthesis product TMPTA or EO3-TMPTA, and the product after the reaction was analyzed by high performance liquid chromatography. The results are shown in the attached Figure 2 and attached Figure 3 As shown, qualitative analysis of organic compounds was performed by infrared absorption spectroscopy. The analysis results showed that the synthetic product system was stable, the synthetic product was light in color and transparent, and the catalyst exhibited good catalytic performance.

[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a bio-based supported superacid solid catalyst, characterized in that: The following steps are involved: S1. Carbonization of biomass raw materials: adding ZnCl2 to the dried biomass raw materials and uniformly mixing the ZnCl2 and the biomass raw materials; then putting the biomass raw materials into a heating device and heating and carbonizing them in a nitrogen environment; and cooling the carbonized biomass raw materials in a nitrogen environment until the temperature of the carbonized biomass raw materials drops to room temperature; then washing the biochar carrier with deionized water for 2-3 times, and drying to obtain the biochar carrier; S2, sulfonation of biomass, putting the biochar carrier obtained after carbonization into a reactor, and adding an excess of sulfonating agent into the reactor, and obtaining a superacid bio-based catalyst after continuous reaction; wherein the ratio of the biochar carrier to the sulfonic acid group is 1g:2mL-1g:10mL; S3. Loading treatment of bio-based catalysts: wrap the bio-based catalyst with a mesh polymer material and insert it into the electrolyte as a cathode. At the same time, insert the loaded metal into the electrolyte as an anode. Power is turned on for electrochemical deposition to electrolyze the loaded metal and form metal nanoparticles on the surface of the bio-based catalyst, thereby obtaining a loaded superacid bio-based catalyst.

2. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The biomass raw material in step S1 is a combination of one or more of corn cobs, rice straw, wood chips, bamboo chips, sugar cane bagasse, and coconut shells.

3. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: In the step S1, the carbonization temperature of the biomass raw material is 200°C-550°C, and the carbonization time is 0.5 hours-5 hours.

4. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The loading metal selected in step S3 is one of Zn or Cu, and the electrolyte used during the reaction is an acid solution of the anode metal; The step S3 further includes removing the outer reticular polymer material after the reaction is completed, and washing the supported superacid biobased catalyst 2-3 times with deionized water, and drying after washing.

5. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The sulfonating agent used in step S2 is concentrated sulfuric acid, the mass fraction of the concentrated sulfuric acid is 98 wt%, the reaction temperature is 170°C-220°C, and the reaction time of the sulfonation reaction is 6 hours-12 hours.

6. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The sulfonating agent used in step S2 is fumed sulfuric acid, the reaction temperature is 120°C-170°C, and the reaction time of the sulfonation reaction is 6 hours-8 hours.

7. The method for preparing a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The sulfonating agent used in step S2 is chlorosulfonic acid, the reaction temperature is 20°C-50°C, and the reaction time of the sulfonation reaction is 6 hours-12 hours.

8. The preparation method of a bio-based supported superacid solid catalyst according to any one of claims 2-4, characterized in that, It also includes the step of performing pretreatment before the step S1, specifically including: cutting, mixing, crushing and drying the biomass raw material; The particle size after crushing is 40 meshes to 80 meshes.

9. The preparation method of a bio-based supported superacid solid catalyst according to claim 1, characterized in that: The length of the biomass raw material after cutting is 3 cm to 4 cm, the drying temperature in steps S1 and S3 is 80°C to 105°C, and the drying time is 3 hours to 5 hours.